Design of Ultrasonic Sensor and Ultraviolet Sensor Implemented on a Fire Fighter Robot Using AT89S52 - Ipin Prasojo; Phong Thanh Nguyen; Omar tanane; Nishith Shahu (Universitas Muhammadiyah Yogyakarta, 2020)
A firefighter is a task given by someone or a team to extinguish a fire that occurs when building a building. The officer took the danger of fighting the fire with a fire engine equipped with a water sprayer. Because of these dangers, a robot was made to help put out the fire. This research aimed to design a fire extinguisher robot using AT89S52 microcontroller as its controller. A DC fan controlled by a relay was utilized to extinguish the fire and a fire sensor (UV-Tron) was used to detect the presence of fire. The robot was driven by motor DC. It could detect the surrounding obstacles and possessed an ultrasound-based navigation system. If the ultrasound system detects an obstacle, the robot will automatically turn without colliding the obstacle or other things around it. The result of the research showed that the proposed fire extinguisher robot can detect fire as far as 5 meters and successfully extinguish the fire.